Exclusive breastfeeding practice and sources of support during COVID-19 pandemic in Indonesia - Cahya Ayu Agustin; Judhiastuty Februhartanty; Saptawati Bardosono (Indonesian Journal of Human Nutrition, 2021)
In 2018, the national coverage of exclusive breastfeeding among infants aged 0-5 months in Indonesia was still low. The COVID-19 pandemic can be a challenge to increase the coverage of exclusive breastfeeding. This study investigated the association between sources of breastfeeding supports and exclusive breastfeeding practices among mothers with infants aged under 6 months during the COVID-19 pandemic in Indonesia. This study used a cross-sectional study design through an online survey from November 2, 2020, to February 8, 2021. A total of 248 subjects were obtained through convenience sampling. Data analysis was done by bivariate analysis using Chi-square or Fisher’s exact test. Most of the subjects were aged 18-34 years old (90.7%), had higher education level (86.7%), had household income range Rp.3,000,000 – Rp.7,199,999 (39.2%), lived in Java Island (83.1%), had an infant aged ≤ 4 months (76.2%), and had a baby boy (51.2%). The proportion of exclusive breastfeeding was 79.0%. The most common sources of breastfeeding support were obtained from husband (91.1%) and health workers (65.7%), followed by family (62.9%). No significant association was found among all support sources on breastfeeding with exclusive breastfeeding. However, the proportion of exclusive breastfeeding among mothers who received husband support (80.1%) was higher than those who did not (68.2%). The most convenient and feasible breastfeeding supports that mother could obtain during pandemics were home-based supports. Mothers, their husbands, and families should be the priority target for health professionals to provide preventive and promotive breastfeeding intervention.